Examining the Effects of Financial Literacy and the Technology Acceptance Model on Fintech Payment Adoption Intention - Samuel Bong; Sumitro Sumitro; Vinsensius Vinsensius (Amkop Management Accounting Review (AMAR), 2026)
This study aims to examine the influence of financial literacy and the Technology Acceptance Model (TAM) on the intention to use fintech services, particularly PayLater, among university students in Pontianak City. Employing a quantitative approach with a descriptive-verificative method, the study involved 150 respondents selected through purposive sampling and analyzed using multiple linear regression. The findings indicate that financial literacy does not have a significant effect on usage intention (sig. 0.092 > 0.05), whereas TAM has a positive and significant effect (sig. 0.000 < 0.05). Simultaneously, both variables significantly influence fintech usage intention (sig. 0.000), with an R² value of 0.295, indicating that 29.5% of the variance in usage intention is explained by financial literacy and TAM. These findings confirm that perceived usefulness and perceived ease of use are the primary factors driving students’ intention to use PayLater, while financial literacy has not yet become a determining factor in fintech adoption behavior.